Effects of Alien Organisms on Growth of Common Carp, Cyprinus carpio Cultivated in Earthen Ponds - Taher, Majid M.; Muhammed, Sadiq J.; Mojer, Ahmed M.; Al-Dubakel, Adel Y.; Al-Noor, Sajed S.; Sabti, Zeki A. (Mesopotamian Journal of Marine Sciences, 2023)
The experiment was conducted at Agricultural Research Station- Aquaculture Unit- Agriculture College- Basrah University in six earthen ponds (600 m3). The stady inclouding of alien organizms effect on growth of common carp Cyprinus carpio. Using an agricultural shadow as a filtering fabric was put in inlets pipes (T1), while T2 without filters. Fishes was daily feeding by a commercial sinking pellets manufactured by Agricultural Consultant Office belonging to Agriculture College, With a ratio of 3% from fishes weight. Total length and weight of fishes were measured at the beginning and at the end of the experiment. The weight of subsamples for fishes were taken periodically and daily feed changed after each weighing. At the end of the experiment the alien organism in all ponds were collected, classified and weighed individualy except shrimp. Results of current experiment revealed that there were significant differences (P≤0.0.5) in final weigh, wight increment, daily growth rate and feed conversion rate between fishes reared in ponds with and without filter. These differences may be related to differences in numbers and weighs of alien organisms in these ponds (97 individuals of six fish species in ponds without filter comparing with two individuals of one fish species in ponds with filter, and also 16314 g of shrimp in ponds without filter comparing with 440 g in ponds with filter). From the results of the current experiment, it can be concluded that culturist must used filters in inlet pipes of their ponds to prevent or reduced the entering of alien organizms to these ponds.